2007
DOI: 10.1111/j.1365-2699.2007.01745.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of altitudinal species richness patterns of bryophytes with other plant groups in Nepal, Central Himalaya

Abstract: Aim To explore species richness patterns in liverworts and mosses along a central Himalayan altitudinal gradient in Nepal (100-5500 m a.s.l.) and to compare these patterns with patterns observed for ferns and flowering plants. We also evaluate the potential importance of Rapoport's elevational rule in explaining the observed richness patterns for liverworts and mosses.Location Nepal, Central Himalaya.Methods We used published data on the altitudinal ranges of over 840 Nepalese mosses and liverworts to interpol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
135
3
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(175 citation statements)
references
References 52 publications
(118 reference statements)
20
135
3
3
Order By: Relevance
“…In any case, species ranges result from complex interactions among many factors, such as physiological traits, the complex evolutionary history of speciation and dispersal, and constraints resulting from continent shape [55]. No general trends appear to exist for Rapoport's elevational rule for all biological organisms, suggesting that the factors determining range size are complex and remain poorly understood [56].…”
Section: Rapoport's Elevational Rulementioning
confidence: 99%
“…In any case, species ranges result from complex interactions among many factors, such as physiological traits, the complex evolutionary history of speciation and dispersal, and constraints resulting from continent shape [55]. No general trends appear to exist for Rapoport's elevational rule for all biological organisms, suggesting that the factors determining range size are complex and remain poorly understood [56].…”
Section: Rapoport's Elevational Rulementioning
confidence: 99%
“…However, the altitudinal relationship is clearly a more complex and often misinterpreted phenomenon (Rahbek 1995(Rahbek , 2005. Vascular plant diversity in vegetation plots typically shows a unimodal altitudinal pattern, with maxima at intermediate altitudes (Minchin 1989;Bhattarai and Vetaas 2003;Grytnes 2003;Grytnes et al 2006;Grau et al 2007). Most such studies reviewed by McCain and Grytnes (2010) revealed this trend, therefore the unimodal species richness-altitude patterns may seem to be universal.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, mountain ecosystems have received increasing attention from researchers examining ecological and biogeographical patterns as well as theories of biodiversity because they provide habitats for various organisms; in addition, a series of environmental gradients in mountain ecosystems are important factors affecting biodiversity and patterns of species distribution [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Of these main types, hump-shaped distribution patterns were recognized as a predominant type. However, most previous studies aimed to clarify mechanisms at very large regional scales such as country and continental scales using secondary distribution data from the literature associated with the study areas [12,14,17].…”
Section: Introductionmentioning
confidence: 99%